Synthesis of new photosensitive H2BBQ2+[ZnCl4]2−/[(ZnCl)2(μ-BBH)] complexes, through selective oxidation of H2O to H2O2 - Stylianou, Marios; Hadjiadamou, Ioanna; Drouza, Chryssoula; Hayes, Sophia C.; Lariou, Ε.; Tantis, Iosif; Lianos, Panagiotis; Tsipis, Athanassios C.; Keramidas, Anastasios D. (My University, 2017)
A new two-electron photosensitizer, H2BBQ2+[ZnCl4]2−/[(ZnCl)2(μ-BBH)] (BBQ stands for 2,5-bis[bis(pyridin-2-ylmethyl)amino]-1,4-quinone and BBH stands for 2,5-bis[bis(pyridin-2-ylmethyl)amino]-1,4-hydroquinone), has been synthesized and the oxidation state of the ligand was determined by X-ray crystallography and NMR spectroscopy. Under light illumination the H2BBQ2+[ZnCl4]2− + ZnCl2 is reduced quantitatively to [(ZnCl)2(μ-BBH)] (pH ∼ 5) oxidizing H2O to H2O2 as is evident by trap experiments. Electrochemistry gave a reversible two-electron ligand-centered redox wave for [(ZnCl)2(μ-BBH)]. UV-Vis, luminescence and EPR spectroscopies reveal the slow formation of a stable quinone diradical, intermediate of the reaction. DFT calculations are in agreement with the proposed mechanism. Based on this property an aqueous {[(ZnCl)2(μ-BBH)]||H2O2} solar rechargeable galvanic cell has been constructed.
Keywords: Monopropellant; Liquid Rocket Propellant; Specific Impulse